Response of species dominance and niche of plant community to wetland degradation along alpine lake riparian - Wu, Shengnan; Dong, Shikui; Wang, Ziying; Li, Shengmei; Ma, Chunhui; Li, Zhouyuan (Frontiers in Plant Science, 2024)
Alpine wetland degradation threatens riparian biodiversity and ecological balance. Our study, conducted in July 2020 along the northern and eastern shores of Qinghai Lake, seeks to unravel the impacts of such degradation on plant species dominance and ecological niches, using advanced network analysis methods to explore the dynamics and survival strategies of plant species. We applied a space-to-time method to delineate three wetland degradation stage: a healthy swamp wetland, a slightly degraded wet meadow, and a degraded dry meadow. Six representative sampling points were chosen. At each point, three sample lines were randomly established, radiating outward from the center of the lake wetland, with each stage of degradation meticulously examined through three replicates to assess the plant communities in terms of species composition, plant height, coverage, and abundance. Our research reveals that species such as Kobresia tibetica and Leymus secalinus exhibit remarkable abundance across various stages of wetland degradation, indicating a robust tolerance to these conditions. This observation, coupled with the complexity of plant community structures in degrading wetlands, suggests that such intricacy cannot be solely attributed to the dominance of particular species. Instead, it is the result of a diverse array of species adapting to fluctuating water levels, which promotes increased species richness. Despite the prominence of species that exhibit rapid growth and reproduction, the ecological significance of less abundant species in contributing to the community's complexity is also notable. Changes in habitat conditions due to wetland degradation facilitate both competitive and cooperative interactions among species, highlighting the dynamic nature of these ecosystems. Our analysis shows no significant linear relationship between the ecological niche overlap values and niche widths of plant species. However, the strategies employed by dominant species for competition and resource acquisition, as observed in the ecological niche overlap networks, underscore the adaptive capacity of plant communities. These insights underscore the need for tailored restoration strategies to conserve the biodiversity of alpine lake riparian ecosystems. This research not only sheds light on the resilience and adaptability of ecosystems in the Qinghai-Tibetan Plateau but also offers valuable lessons for the conservation of similar habitats worldwide.